Chapter 7: EU-Russia energy relations amidst war and the green transition: a paradigm change? - Siddi, Marco (Edward Elgar Publishing, 2023)
As the EU unveiled the Green Deal and its new climate agenda between 2019 and 2021, long-term prospects for fossil fuel exporters to the European market began to look grim. The EU's 2030 climate and energy framework and its 2050 climate neutrality target imply a drastic reduction in imports of coal, first, and then oil and gas. Russia's attack on Ukraine in February 2022 has led the EU to focus on reducing energy imports from Russia. Therefore, the long-standing energy relationship between the EU, its member states and Russia could be entering its conclusive phase. Moreover, the war in Ukraine has led to the freezing of the nascent debate concerning cooperation between the EU and Russia in 'green' sectors, such as hydrogen production and trade. The chapter assesses current developments and what they mean for the European energy sector.